1999
DOI: 10.1046/j.1365-2249.1999.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of JAK2 signal transductional pathway in activation and survival of human peripheral eosinophils by interferon-gamma (IFN-γ)

Abstract: The purpose of this study was to determine whether the JAK pathway is involved in eosinophil activation and survival through IFN-gamma receptor signalling in human peripheral eosinophils. Eosinophils were purified from the blood of six atopic disease patients by anti-CD16 magnetic bead-negative selection. IFN-gamma significantly up-regulated survival and CD69 expression in 24-48 h cultured eosinophils. Further, IFN-gamma induced tyrosine phosphorylation of JAK2 in eosinophils, as indicated by Western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…For instance, JAK2-deficient cells are still responsive to IL-6 (67), but fail completely to respond to IFN-␥, indicating a critical, nonredundant role of JAK2 in the IFN-␥-signaling pathway. In light of our observations that IL-6 failed to induce HMGB1 release and that a specific inhibitor of JAK2, AG490 (69,70), abrogated IFN-␥-induced FIGURE 7. Conceptual relationships between IFN-␥, JAK2, TNF, and HMGB1 release in macrophage cultures.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, JAK2-deficient cells are still responsive to IL-6 (67), but fail completely to respond to IFN-␥, indicating a critical, nonredundant role of JAK2 in the IFN-␥-signaling pathway. In light of our observations that IL-6 failed to induce HMGB1 release and that a specific inhibitor of JAK2, AG490 (69,70), abrogated IFN-␥-induced FIGURE 7. Conceptual relationships between IFN-␥, JAK2, TNF, and HMGB1 release in macrophage cultures.…”
Section: Discussionmentioning
confidence: 90%
“…IFN-γ has been shown to prolong peripheral eosinophil survival [4]and to induce CD69 on cultured peripheral eosinophils, one of the eosinophil activation markers [8]. We have reported that binding of IFN-γ to peripheral eosinophils initiated a series of events that resulted in the rapid tyrosine phosphorylation of not only the IFN-γRα chain but also JAK1, JAK2 and STAT1α [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that induction of CD69 expression on peripheral eosinophils by IFN-γ depends on tyrosine phosphorylation of JAK2, using a specific inhibitor, AG-490 [4]. Although there is no specific inhibitor against tyrosine phosphorylation of STAT1α, Lee and Benveniste [5]showed that STAT1α was involved in IFN-γ induction of the class II transactivator and class II MHC gene using an antisense oligonucleotide against STAT1α.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a specific JAK2 inhibitor, AG490 [15], has been shown to block the anti-apoptotic effect of IFN-γ on peripheral eosinophils [16, 17]. We have previously found that AG-490 could significantly inhibit IL-5- or IFN-γ-induced CD69 expression on peripheral eosinophils [7]. In the present study, we showed that AG-490 could also inhibit the induction of CD69 expression and the tyrosine phosphorylation of JAK2 in eosinophil precursors.…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently shown that induction of CD69 expression on eosinophils by IFN-γ and prolongation of cell survival depend on tyrosine phosphorylation of JAK2 [7]. On the contrary, we found that IFN-γ inhibits IL-3- and IL-5-induced eosinophil differentiation from progenitor cells [8].…”
Section: Introductionmentioning
confidence: 90%